(3GdChSW GdcHjQs - (3eMeO Hf eMeO Hf WQNGf Hf ChRdZ, CHh fUQ GdaGQGHqj, hjYQa HGdeYde GdKGfj,J (B339 (3g` s
(3ChdgG (B:s
(3bGd CHh fUQ UfGYI GdLOd gi GdfUGYI GdJi HgG jMUd ddEfSGf GdbhI Ydi Cf jYed ef ebOeGJ eTghQI s
(3BNQgG (B:s
(3Cf jchf eY Pdc bjGSGJ hjHWd GdBQGA GdJi JUGObJgG GdadGSaI ajeG Hjfge Ch UGQ GdLeghQ ajgG s
(3Vef eLehY , JQJjHgG (B: (3GdMGOi hGdYTQhfs
(3GdfSNI HgG MhGTs
(3GfXQ GdeNWhW Qbe (B305s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B194s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(240 / 15) s
Keywords: (3GdadSaI hGdefWbs